Patterns of drug use among a sample of drug users and injecting drug users attending a General Practice in Iran - Day, Carolyn (BioMed Central, 2006)
AIM: This study aimed to examine drug use, drug treatment history and risk behaviour among a sample of Iranian drug users seeking treatment through a general practice clinic in Iran. METHODS: Review of medical records and an intake questionnaire at a large general practice in Marvdasht, Iran, with a special interest in drug dependence treatment. Records from a random sample of injecting drug users (IDU), non-injecting drug users (DU) and non-drug using patients were examined. RESULTS: 292 records were reviewed (34% IDU, 31% DU and 35% non-drug users). Eighty-three percent were males; all females were non-drug users. The mean age of the sample was 30 years. Of the IDU sample, 67% reported sharing a needle or syringe, 19% of these had done so in prison. Of those who had ever used drugs, being 'tired' of drug use was the most common reason for seeking help (34%). Mean age of first drug use was 20 years. The first drugs most commonly used were opium (72%), heroin (13%) and hashish/ other cannabinoids (13%). Three quarters reported having previously attempted to cease their drug use. IDU were more likely than DU to report having ever been imprisoned (41% vs 7%) and 41% to have used drugs in prison. CONCLUSION: This study has shown that there is a need for general practice clinics in Iran to treat drug users including those who inject and that a substantial proportion of those who inject have shared needles and syringes, placing them at risk of BBVI such as HIV and hepatitis C. The expansion of services for drug users in Iran such as needle and syringe programs and pharmacotherapies are likely to be effective in reducing the harms associated with opium use and heroin injection.